APLIKASI BEBERAPA PUPUK ORAGANIK PADA TANAH MARJINAL DENGAN INDIKATOR TANAMAN BAYAM DI KOTA MANADO - Karamoy, Theffie Lientje; Kumolontang, W. J. N.; Kaunang, Djoni (EUGENIA, 2019)
The study aims to determine the effect of providing various types of organic fertilizer on the growth of spinach on marginal soils. Held in the Faculty of Agriculture greenhouse for pot experiments. Soil analysis, manure and compost are done in the Laboratory. Research using the RAL method A = Control B = Chicken manure 30 tons / ha, C = Cow Manure 30 tons / ha, D = Pig manure 30 tons / ha, E = Goat Manure 30 tons / ha and F = Compost 30 tons / ha per treatment added with sand. The study was conducted with 3 replications obtained 18 experimental pots. The data obtained were analyzed by analysis of variance and if there was a real influence continued with the LSD test of 5%. The results showed, the provision of various types of organic fertilizer on marginal soils significantly affected the availability of nutrients needed by plants in the growth and production of spinach plants in this case plant height, number of leaves, fresh weight of plants.